Market volatility in response to merger and acquisition announcements: Evidence from selected industries in the Philippine market - Romero, Frederick P. (Animo Repository, 2017)
In order to cater to more consumers and markets, both locally and internationally, companies perform various corporate actions that can greatly help them in business expansion, cost-saving, market valuation, operation efficiency, and research and development. One of these corporate actions is Mergers and Acquisition (M&A). This study examines the impact of M&A event announcements on the short-term stock valuation of the acquiring firm. The study covers all announced M&A events in the Philippines from 2007 to 2015 across five (5) major industries namely: Materials, Property, Consumer Staples, Energy and Financials. Event study methodology was used to determine the significance of the event across −1/+1, −3/+3, −5/+5, −10/+10 and −15/+15 for the event windows. Inferential statistics is set at the.01,.05 and.10 level of significance using Generalized Rank Test, two-tailed. Across all the industries used, only the companies under the Financial sector experienced significant negative abnormal returns across the 31-day event window. The results imply that the investors of most of the industries did not view the M&A event as something that will significantly influence the company’s market valuation. In addition, the overall impact of the event may not be well-disseminated to the market, thus, the investors were not able to determine the M&A’s significance on the overall value of the firm. Investors may use the results of this study in order to properly manage their portfolio during an M&A event in order to maximize their profit or minimize their investment risks. © 2017 American Scientific Publishers. All rights reserved.